Propiedades electromagnéticas de neutrinos y violación de Lorentz - Gallardo García, Ricardo Daniel (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
According to the Standard Model, neutrinos are massless elementary particles, of half-integer spin, and electrically neutral; they are partners of the SU(2)L doublet of their corresponding charged leptons. There are 3 different types of neutrinos: the electronic neutrino the muonic and the tauonic ones. Nevertheless, due to the experiments performed by Davis and co-workers on solar neutrino fluxes since the late sixties of last century, nowadays, we know that neutrinos must be massive particles. Neutrinos are important particles for explaining different phenomena such as the beta decay process, or thermonuclear processes on astrophysics and cosmology or in nucleus-synthesis in the early universe. The neutrinos interact very weakly so it is very difficult to detect them. In this master thesis we study static electromagnetic properties of neutrinos, even though they are neutral particles, can couple to electromagnetic fields due to their magnetic dipole moment. We will focus on the process: νi −→ νj + γ, this process only makes sense as a quantum fluctuation process. The calculation that will be realized will take at the one loop level in the Minimum Extended Standard Model with CPT and Lorentz violation, from which we can extract the contributions to the dipole moment of the neutrino.

De acuerdo al Modelo Estándar, los neutrinos son partículas elementales de espín un medio, sin carga y sin masa; es el compañero del doblete de su leptón cargado. Existen 3 diferentes tipos de neutrinos: el neutrino del electrón, del muón y del tau. Sin embargo, debido a las mediciones de Davis y colaboradores sobre el flujo de neutrinos solares que empezó a realizar a finales de los sesentas del siglo pasado, hoy sabemos que deben tener masa. Los neutrinos son importantes para explicar diferentes fenómenos como el proceso de decaimiento beta, o procesos termonucleares en la astrofísica y la cosmología o la núcleo-síntesis en el universo temprano. Los neutrinos interactúan muy débilmente, es por ello que son difíciles de detectar. En este trabajo de tesis de maestría, estudiamos propiedades electromagnéticas estáticas de los neutrinos, ya que a pesar de que son partículas neutras se pueden acoplar a campos electromagnéticos mediante su momento dipolar magnético. Nos centraremos en el proceso νi −→ νj + γ, el cual solo tiene sentido como un proceso de fluctuación cuántica. El cálculo que se realizara lo llevaremos a nivel de un rizo en el Modelo Estándar Mínimamente Extendido con violación CPT y Lorentz, de donde podremos extraer las contribuciones al momento dipolar eléctrico y momento dipolar magnético del neutrino.
Facultad de Ciencias Físico Matemáticas. Maestría en Ciencias en Ingeniería Física
Keywords: info:eu-repo/classification/cti/1; FISMAT-M-2018-0225; Neutrinos; Momento dipolar; Fluctuación cuántica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3297